Determinants of Profitability of Health Companies Listed on the Indonesia Stock Exchange - Septyaningtyas, Dinar Rika; Marwanto, IGG Heru (Universitas Nusantara PGRI Kediri, 2024)
Research aim: The study aimed to identify the effect of leverage, liquidity, and company size on the profitability of health companies listed on the Indonesia Stock Exchange. Design/Methode/Approach: This research is a type of explanatory research using a quantitative approach. The study population is all health companies listed on the Indonesia Stock Exchange in 2017 – 2021. Purposive sampling techniques were used in this study so 12 companies were used as research samples. The data analysis method used the multiple linear regression test using SPSS Research Finding: The results showed that Leverage negatively affects the Profitability of Health companies on the Indonesia Stock Exchange 2017-2021. Liquidity has a significant positive effect on profitability. The size of the company has a significant positive impact on the Profitability of the Company. Research limitation: The variables of this study are only limited to Leverage, Liquidity, and Company Size.